A case report of familial type 2 diabetes mellitus combined with hypothyroidism and multiple autoimmune diseases - Su, Xuan; Yang, Yang; Jiang, Haotian; Lai, Xiuchang; Qu, Yujia (Frontiers in Endocrinology, 2025)
Gene mutations in the Janus kinase/signal transducer and activator of transcription signaling (JAK/STAT) pathway can promote the occurrence of type 2 diabetes mellitus (T2DM) and autoimmune diseases. We report on two patients with T2DM (a mother and her adult son) with concomitant Hashimoto’s thyroiditis and autoimmune diseases. The son was diagnosed with systemic sclerosis and antiphospholipid syndrome, while the mother was diagnosed with primary biliary cholangitis. Both diagnoses occurred simultaneously. These cases highlight that, in clinical practice, careful symptom assessment, thorough history-taking, standardized physical examination, and obtaining a detailed family history are important. This reduces the misdiagnosis and missed diagnosis rates, enabling early diagnosis and treatment, thereby improving patient outcomes. While genetic testing was not performed in these two patients, this represents a potential direction for future research.